Discourse and Intercultural Miscommunication: Arguments for Discourse Acquisition - Polina V. Vinogradova (Asociación Colombiana de Profesores de Ingles, 2016)
Regarding second language acquisition, researchers discuss a rather wide range of theories and language phenomena, investigate the nature of grammar and lexicon acquisition, and study pragmatic issues of language use. Moreover, the cultural underpinnings of language use appear to be closely connected to aspects of second language acquisition. It is a rather common situation in which a non-native speaker (NNS) is able to use grammar constructions appropriately, has a reach of vocabulary, and seems to have a very good command of the foreign language in general, but fails in his/her efforts to communicate effectively with native speakers (NS).